Policy-driven success: Scaling livestock innovations in Son La Province, Vietnam - International Livestock Research Institute; International Center for Tropical Agriculture; Son La Sub-department of Animal Health (International Livestock Research Institute, 2024)
The CGIAR Initiative on Sustainable Animal Productivity (2022–2024) in Son La Province has made significant achievements in improving livestock production in Mai Son District. Achievements include training over 5,000 people on animal health, breed selection and sustainable farming techniques. The project inseminated 170 cows, improving pregnancy rates, and established 8 biosecurity demonstration farms. It also introduced sustainable feed practices, training 2,000 farmers on grass cultivation to prevent soil erosion. Local authorities co-invested in the project, ensuring its sustainability and long-term impact, which will continue to improve farmers' livelihoods and support regional development after the project's completion.